2008
DOI: 10.1029/2008gl034575
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric impact of reflected planetary waves from the stratosphere

Abstract: A reflection of stratospheric planetary waves and its impact on the troposphere during a stratospheric sudden warming of March 2007 are investigated. Zonal propagation and reflection of the planetary waves is clearly seen in the longitude‐height sections of the eddy geopotential height and the vertical and zonal component of the three‐dimensional wave activity flux. A wave packet propagating upward and eastward from Eurasian continent was reflected by a negative wind shear in the upper stratospheric westerly j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 15 publications
8
63
0
1
Order By: Relevance
“…This trapping was also associated with the development in the troposphere of a trough over the Atlantic sector and a ridge over the Eurasian sector, leading to the formation of a blocking there. Such a change in the wave structure is similar to that observed following planetary wave reflection events (Shaw and Perlwitz, 2013;Kodera et al, 2008Kodera et al, , 2013, although the pattern was somewhat shifted eastward in the present case. In the usual case, an initial change in the zonal-mean zonal wind field in the stratosphere is created by a stronger upward propagation of planetary waves from the troposphere (Kodera et al, 2016a).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 64%
See 1 more Smart Citation
“…This trapping was also associated with the development in the troposphere of a trough over the Atlantic sector and a ridge over the Eurasian sector, leading to the formation of a blocking there. Such a change in the wave structure is similar to that observed following planetary wave reflection events (Shaw and Perlwitz, 2013;Kodera et al, 2008Kodera et al, , 2013, although the pattern was somewhat shifted eastward in the present case. In the usual case, an initial change in the zonal-mean zonal wind field in the stratosphere is created by a stronger upward propagation of planetary waves from the troposphere (Kodera et al, 2016a).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 64%
“…The influence of downward penetration of zonal winds from the polar stratosphere, such as the annular modes (Baldwin and Dunkerton, 1999;Thompson and Wallace, 2001) or the polar night jet (PNJ) oscillation (PJO) Kodera, 1999, 2004;Hitchcock et al, 2013), has been well documented. More recently, the connection between tropospheric weather and changes in planetary wave structure in the polar region, due to reflection or downward propagation in the polar region, has also been reported (Perlwitz and Harnik, 2003;Shaw and Perlwitz, 2013;Kodera et al, 2008Kodera et al, , 2013Kodera et al, , 2016a. Although stratosphere-troposphere coupling in the tropical region is more controversial, a possible connection has been proposed based on the modulation of deep convective activity by the stratospheric quasi-biennial oscillation (QBO) (Collimore et al, 2003;Liess and Geller, 2012;Yoo and Son, 2016) and sudden stratospheric warming (SSW) (Kodera, 2006;Eguchi and Kodera, 2010;Kodera et al, 2015;Eguchi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[18] Kodera et al [2008] reported on the impact of reflected stratospheric planetary waves on the Canadian trough. Although not discussed in that article, this accompanies the development of Pacific ridge which leads to a formation of blocking.…”
Section: Planetary Waves and Blockingmentioning
confidence: 99%
“…[19] The impacts of the reflection of planetary waves from the stratosphere were investigated in Kodera et al [2008]. In that study, only planetary-scale (with zonal wave components of wave numbers 1 to 3) eddies were examined.…”
Section: March 2007 Eventmentioning
confidence: 99%
“…For example, Baldwin and Dunkerton (2001) revealed that the signals of the polar vortex propagate downward from the stratosphere to the troposphere over one to two months. The mechanisms of the downward influence are still contentious, though some theories have been proposed: wave-mean flow interaction (Kuroda and Kodera 1999), reflections of planetary waves due to the change in stratospheric circulation (Perlwitz and Harnik 2003;Perlwitz and Harnik 2004;Kodera et al 2008), influence of the stratospheric potential vorticity (PV) anomaly (Ambaum and Hoskins 2002), and so on (please refer to Kidston et al 2015 for a holistic review). Among these, Ambaum and Hoskins (2002; hereafter AH02) suggested a mechanism in which the modulation of the stratospheric circulation affects the troposphere via geostrophic adjustment.…”
Section: Introductionmentioning
confidence: 99%